Effects of different dose of nitrogen and lime on soil properties and maize (Zea mays L.) on acidic nitisols of Northwestern Ethiopia - Amare, Birtukan; Molla, Eyayu; Selassie, Yihenew G.; Belay, Habtamu Tadele; Bayu, Tesfaye (Journal of Agriculture and Natural Resources, 2022)
This study was carried out on the nitisols of Burie district, Ethiopia to examine the effect of integrated use of lime and nitrogen on soil physicochemical properties and maize yield. Two levels of lime (0 and 0.5 t/ha) and five-level of nitrogen (0, 46, 92, 138 and 184 kg N/ ha) were laidout in randomized complete block design with three replications. The results indicated that among before planting, soil bulk density (BD), pH, soil organic carbon (OC), total nitrogen (TN), available P and CEC were 1.42 g/cm3, 5.2 (strongly acidic), 1.32% (very low), 0.12% (low), 8.86 mg /kg (very low), and 19.57 cmolc /kg (medium), respectively. The physicochemical properties except bulk density increased. The lowest soil BD (1.21 g/m3) was from plots treated with 0.5 t/ha lime and 184 kg N/ ha. The maximum soil pH (6.85) was obtained from plots treated with 184 kg N/ ha and 0.5 t/ha lime. The maximum soil CEC (35.38 (cmolc /kg) was obtained from plots treated with 184 kg N/ ha and 0.5 t/ha lime. Level of lime, nitrogen fertilizer, and interaction effects of lime and nitrogen fertilizer (L×N) significantly affected maize yield (p<0.001). Indeed yield of maize has positive correlations with most soil physicochemical properties but negative with BD (r= -0.543). The adjusted yield and net benefits was 6.4 t/ha and 1101.77. Inherent physicochemical properties of the soil are changed either by sole or combined use of lime and N fertilizer. Soils tilled with 0.5 t/ha lime and 138 kg/ha nitrogen were found in maximum net benefit. Residual long-term effects should be researched. Thus, liming should be given an emphasis on acidic soil amelioration. Moreover, the government may facilitate the supply of lime and nitrogen fertilizer to the farmers.